Micro and macroscale analyses for prognosis of composite structures : a new physics based multiscale methodology - Sartorato, Murilo (2018)
Currently, one of the greatest challenges for the areas of Material Sciences and Structural Engineering is to perform accurate analysis for prediction of damage in composite materials, the evolution of damage and failure. Although several models and failure criterion already exist for the simulation of damage in composite materials, most models do not produce acceptable results for detailed designs. The models currently in use often under or overestimate loads required for the degradation and failure. This occurs as most of these models is based upon phenomenological or semi-empirical data, which adjust failure surfaces or failure envelopes to experiments. This approach neglects the inherent anisotropy and heterogeneity of composite materials, which cause several failure mechanisms to occur simultaneously in different materials scales and phases. One possible solution to this problem is to use and/or develop new damage and failure models based on multiscale approaches and physical failure mechanisms based on Continuum Fracture Mechanic. In this scenario, the main objective of the present work consists on studying and developing multiscale based damage models applied to composite structures manufactured with unidirectional fibers under different load cases: pure tensile, pure bending, mixed tensile-bending and multiaxial. For the development of these models, works found in the literature were critically evaluated and new formulations were studied, adapted and improved upon. The basic methodology is based on using homogenization techniques to obtain degenerated elastic properties from damaged Representative Volume Elements (RVEs); the damage profile of the RVE is defined as intralaminar cracks parallel to the fiber directions and is calculated using a multiscale approach. The multiscale approach comprehends three separate models, one in the macroscale for the calculation of accurate stress/strain states in the critical points, and two in the microscale for the prediction of intralaminar damage (matrix cracking). These models interact between themselves, as the results from each one are used as boundary conditions for the other in a computational analysis loop over load steps via an iterative process. The developed models were implemented either stand-alone Python codes or into the finite element analysis package AbaqusTM using its automatization capabilities with Python scripts, as well as subroutines in Fortran (UEL - User Element Subroutine) linked to commercial finite element package AbaqusTM